Endocytosis and Enamel Formation - Pham, Cong-Dat; Smith, Charles E.; Hu, Yuanyuan; Hu, Jan C-C.; Simmer, James P.; Chun, Yong-Hee P. (Frontiers in Physiology, 2017)
Enamel formation requires consecutive stages of development to achieve its characteristic extreme mineral hardness. Mineralization depends on the initial presence then removal of degraded enamel proteins from the matrix via endocytosis. The ameloblast membrane resides at the interface between matrix and cell. Enamel formation is controlled by ameloblasts that produce enamel in stages to build the enamel layer (secretory stage) and to reach final mineralization (maturation stage). Each stage has specific functional requirement for the ameloblasts and ameloblasts adopt different cell morphologies during each stage. Protein trafficking including the secretion and endocytosis of enamel proteins is a fundamental task in ameloblasts. The sites of internalization of enamel proteins on the ameloblast membrane are specific for every stage. In this review, an overview of endocytosis and trafficking of vesicles in ameloblasts is presented. The pathways for internalization and routing of vesicles are described. Endocytosis is proposed as a mechanism to remove debris of degraded enamel protein and to obtain feedback from the matrix on the status of the maturing enamel.